Mekanisme Corporate Governance dan Corporate Social Responsibility terhadap Tax Avoidance pada Perusahaan Sektor Pertambangan Batu Bara - Alifia Syahdarani Kirana; Siti Sundari (Journal of Management and Bussines (JOMB), 2022)
This study aims to empirically examine the effect of corporate governance mechanisms as proxied by institutional ownership, independent commissioners, and audit committees as well as the implementation of corporate social responsibility on tax avoidance. This research method is descriptive communicative. The research was conducted on coal mining sector companies listed on the IDX for the 2017-2019 period. The research data used is secondary data obtained from the annual report. The research sample is 66 annual reports from 22 coal mining sector companies. The research data was processed and analyzed using SPSS 25 software. The data analysis method used descriptive statistics and multiple linear regression. The results showed, a) the t-value of institutional ownership was 1.023 with a significance value of 0.310>0.05; b) the t value of the independent board of commissioners is 0.527 with a significance value of 0.600>0.05; c) the audit committee t value is 0.213 with a significance value of 0.832>0.05; d) the t value of CSR is negative at -0.265 with a significance value of 0.792>0.05. In conclusion, the corporate governance mechanism which is proxied by institutional ownership, independent board of commissioners, and audit committee as well as corporate social responsibility does not contribute to tax avoidance in coal mining sector companies listed on the IDX. Keywords: Corporate Governance, Corporate Social Responsibility, Independent Board of Commissioners, Institutional Ownership, Audit Committee